Heterogeneous Associations Between Pandemic-Induced Socioeconomic Hardships and COVID-19 Vaccine Uptake by Sexual Orientation and Gender Identity: A Nationally Representative Analysis in the United States - JungHo Park; Byoungjun Kim (Vaccines)
Background/Objectives: Socioeconomic hardship during the COVID-19 pandemic was associated with lower vaccine uptake. Since the pandemic has exacerbated socioeconomic challenges faced by sexual and gender minority populations, including employment income loss, housing instability, food insufficiency, and household expense difficulty, this study investigated the disparities in COVID-19 vaccine uptake among these populations. Methods: Using the U.S. Census Bureau Household Pulse Survey, a nationally representative sample of 1,767,966 individuals (6% gay or lesbian, 4.2% bisexual, 1.6% something else, and 90.6% heterosexual respondents), we quantified the COVID-19 vaccine uptakes among sexual and gender minorities, as well as the effect measure modifications by socioeconomic hardships. Results: Despite higher vaccine uptake rates among sexual and gender minorities compared to their heterosexual counterparts, socioeconomic hardships triggered by the pandemic among these populations were associated with decreased vaccine uptake. Importantly, the effect measure modifications by socioeconomic hardships were more pronounced among sexual and gender minority status compared to heterosexual individuals. Conclusions: These results highlight the critical need to address socioeconomic hardships among sexual and gender minorities to enhance vaccine uptake, along with the pre-existing and exacerbated social and economic disadvantages during the COVID-19 pandemic.